Comparing Outcomes in Orthognathic Surgery Using Clear Aligners Versus Conventional Fixed Appliances. Issue 5 (July 2019) - Kankam, Hadyn; Madari, Sarika; Sawh-Martinez, Rajendra; Bruckman, Karl C.; Steinbacher, Derek M.
Abstract : Purpose: Orthognathic surgery for dentofacial deformities is typically preceded and followed by orthodontic treatment. Traditionally, orthodontic hardware is secured to the dentition to allow dental movement and stabilization. Clear-aligner therapy (eg, Invisalign) provides an aesthetic alternative, consisting of a series of transparent trays. Its use has not been described in complex triple-jaw orthognathic surgery. The purpose of this study is to evaluate perioperative outcomes and 3-dimensionally quantify postoperative edema in Invisalign patients undergoing triple-jaw orthognathic procedures, comparing this to patients treated with conventional fixed appliances. The surgical approach to patients with clear-aligners is also outlined. Methods: The authors conducted a retrospective chart review and 3-dimensional morphometric study of Invisalign patients undergoing triple-jaw surgery (LeFort I osteotomy, bilateral sagittal split osteotomy, and genioplasty). An identical assessment of demographically matched patients treated with conventional fixed appliances was performed and compared with the Invisalign group. Results: Thirty-three patients, with a mean age of 19.99 years, were included: 13 with Invisalign and 20 with conventional fixed appliances. No significant difference was observed in operating time, concurrent extraction of teeth, fat grafting, duration of hospital stay, diet advancement, and use of narcotic analgesics between the 2 groups. Nine patients had sufficient 3-dimensional images for volumetric analysis (4 with Invisalign and 5 with conventional fixed appliances). Postoperative edema was not significantly different ( P = 0.712) when comparing conventional fixed appliances (44.29 ± 23.16 cm 3 ) to Invisalign (37.36 ± 31.19 cm 3 ). Conclusion: The present study demonstrates that complex multiple-jaw orthognathic procedures can be successfully performed in Invisalign patients. Perioperative and short-term clinical outcomes are not compromised. Abstract : Supplemental Digital Content is available in the text